Validação brasileira da escala de autocompaixão como estado - Lauriano, Cecília (2025)
The present cross-sectional and quantitative study validated the Brazilian Self-Compassion Scale as a state. This scale, which comprises six dimensions (self-kindness, self-judgment, mindfulness, over-identification, shared humanity, and isolation), allows for monitoring the evolution of self-compassion over time and provides an important contribution to the evaluation of interventions aimed at increasing self-compassion, particularly in experimental studies. Based on 606 responses from Brazilian participants who had Portuguese as their native language, the study employed confirmatory factor analysis and exploratory structural equation modeling, including bifactor models. Findings supported the validity and reliability of the scale across its six proposed dimensions, identifying a dominant general self-compassion factor over specific dimensions. Both the long version (with 18 items) and the short version (with 9 items) as well as the dimension subscales were validated. The observed evidence also confirmed the discriminant validity among the self-compassion dimensions, as well as the predictive and discriminant validity of the self-compassion measure in relation to the Positive and Negative Affect Schedule (PANAS). These results pave the way for understanding antecedent factors and effects of self-compassion in the Brazilian context, thereby contributing to the mental health and well-being of this population